Variable Angle Modular Pillow Unit Design with Adjustable Head and Neck Support Improved for Patients Who Have Undergone Open Heart Surgery - Demet BAL; Sinan KOSE; Dilek ÇİLİNGİR (Atatürk University, 2021)
Aim: The aim of this study is to design the modular pillow unit which is used by patients who have undergone open heart surgery and cannot lie horizontally, easily mounted on different bedstead systems, minimize the negative effects due to pillows that support the head and neck regions in patient's sleep etc. periods and to analyse critical regions during the application and optimization of the design by using computer-aided motion analysis, finite element method. Method: The boundary conditions of the design were determined by reviewing the literature for the problems of patients who undergone open heart surgery due to inability to lie in the supine position in the postoperative period. Represent the head and neck regions modelled by Computer Aided Design (CAD) software and graphs of motion characteristics such as the angular velocity of the head were obtained in the right and left fall movements of the head. The maximum von-Mises stress values of the modular pillow unit were determined by the finite element analysis method and critical regions of the system were determined and finally, the final design of the modular pillow unit was achieved through optimization studies. Results: In the motion analysis of the designed modular pillow unit, when the head of the patient falls to the right / left sides, the side pillow sections slow down and reset the head rate. The motion damping elements of the side pillow units were able to stop the patient's head without falling to the shoulder level. The finite element analysis determined the areas of the design that were subjected to maximum stress. The maximum von-Mises tensile value in the side pillow units is 490.46 MPa which is seen in the damping elements in the recording systems. The fact that the maximum tensile value is below the yield strength indicates that the system is below the safe value. Conclusions: Modular pillow unit can increase the comfort of patients by side pillow unit which prevents falling of the patient's head on the right/left side reflexively during resting and sleeping and preventing sliding the pillows from the head area of the patient.